1985
DOI: 10.1115/1.3261094
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Squeeze Film Damped Multi-Mass Flexible Rotor Bearing Systems

Abstract: A technique is presented for investigating the stability of and the degree of damping in the circular synchronous orbit equilibrium solutions pertaining to radially symmetric multi-mass flexible rotor bearing systems. It involves the analysis of appropriate linearized perturbation equations about the equilibrium solutions and is applicable to systems with several squeeze film dampers. For a system with a single damper, stability threshold maps, independent of unbalance distribution, may be found in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…4 and on the section CD are unstable as the modulus of the first Floquet multiplier is larger than one. These results are identical to those given by McLean and Hahn (1985), but they did not identify the type of the predicted instability or the possible stable rotor responses in these regions.…”
Section: Concentric Damper Operationsupporting
confidence: 87%
“…4 and on the section CD are unstable as the modulus of the first Floquet multiplier is larger than one. These results are identical to those given by McLean and Hahn (1985), but they did not identify the type of the predicted instability or the possible stable rotor responses in these regions.…”
Section: Concentric Damper Operationsupporting
confidence: 87%
“…The rigid critical speed of the #exible rotor system is the pin}pin critical speed when both ends of the #exible rotor are mounted rigidly; the #exible critical speed of the #exible rotor system is the translational critical speed when both ends of the #exible rotor are mounted on the centralizing springs. By using a perturbation method as in reference [3], it is shown that the largest and smallest solutions shown in solid lines are stable and the medium one shown in dotted line is unstable.…”
Section: Solution Of Synchronous Circular Centred-orbit Motionmentioning
confidence: 98%
“…In this case, the continuous rotor model is discretized and a finite number of DOFs are introduced. The dynamics of multi-mass and multi-degrees of freedom (MDOF) rotors supported with SFDs is theoretically studied in [43,44]. The precedent studies assumed that the effect of lubricant inertia on the fluid film reaction forces in SFDs is negligible and either used the complete or the approximate (i.e., long bearing and short bearing approximations) Reynolds equation to represent the SFD dynamics.…”
Section: Introductionmentioning
confidence: 99%